Kajian Ekonomi Penanganan Sedimen Pada Waduk Seri Di Sungai Brantas (Sengguruh, Sutami Dan Wlingi) - Djajasinga, Viari; Masrevaniah, Aniek; Juwono, Pitojo Tri (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Sengguruh, Sutami and Wlingi, were series of three reservoirs in the upper Brantas River which have a high rate of sedimentation, thus research should be carried out to determine the proper method of sediment handling which could maintain the benefit function of reservoirs as well as feasible from economic perspective.Processing data and data analysis was performed to determine the condition of reservoir capacity, sedimentation rate, the amount of sediment handling and most feasible alternatives on sediment handling. The analyzes carried out in two phases, first phases to the existing condition and the second phases to four (4) alternatives of sediment handling at ten years project work. Alternative 1 is sediment handling with a volume of 1 million cum/year, while Alternative 2, Alternative 3, and Alternative 4 is sediment handling with volume equals to annual sedimentation rate with variation on different work method. The average sedimentation rate in those reservoirs on the last 20 years reaching a massive 1.7 million cum/ year. Hence, routine sediment handling with dredging and flushing work should to be done with minimal volume at 1.7 million cum/year. The result of economic analysis show that alternative 3 with B/C = 1.03, IRR = 17.35% and NPV = Rp. 6.37 Billion in the alternative with volume of sediment handled equals to sedimentation rate and feasible from economic perspective.Keywords: reservoir sedimentation, sediment handling, economic benefit.